2018
DOI: 10.1002/adma.201704007
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Strategies of Cancer Therapy Based on Ferroptosis

Abstract: Ferroptosis, a new form of regulated cell death that is iron- and reactive oxygen species dependent, has attracted much attention in the research communities of biochemistry, oncology, and especially material sciences. Since the first demonstration in 2012, a series of strategies have been developed to induce ferroptosis of cancer cells, including the use of nanomaterials, clinical drugs, experimental compounds, and genes. A plethora of research work has outlined the blueprint of ferroptosis as a new option fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
433
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(452 citation statements)
references
References 76 publications
1
433
0
Order By: Relevance
“…These discoveries pave the way for nanoparticle‐triggered ferroptosis. In recent years, ferroptosis mechanism has been taken into consideration for nanomedicine‐mediated cancer therapy, exemplified by the rapid development of nano ferroptosis inducers …”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…These discoveries pave the way for nanoparticle‐triggered ferroptosis. In recent years, ferroptosis mechanism has been taken into consideration for nanomedicine‐mediated cancer therapy, exemplified by the rapid development of nano ferroptosis inducers …”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%
“…In recent years, ferroptosis mechanism has been taken into consideration for nanomedicine-mediated cancer therapy, exemplified by the rapid development of nano ferroptosis inducers. [112,113] For designing of nano ferroptosis inducers, an intuitional method is to incorporate small molecule ferroptosis inducers into nano delivery vehicles. Compared with free drugs, nanoplatforms enable improved solubility and biocompatibility, as well as increased tumor accumulation by either active or passive targeting.…”
Section: Nanoparticle Inducersmentioning
confidence: 99%
“…These ferroptosis inducers exert antitumor activities in many types of malignancies (Dachert, Schoeneberger, Rohde, & Fulda, 2016; Sato et al, 2018; Shintoku et al, 2017), including HCC (Nie, Lin, Zhou, Wu, & Zheng, 2018; Sun et al, 2016). Although inducing ferroptosis is a promising anticancer strategy, the negative regulators of ferroptosis which inhibit cellular iron uptake and/or limit ROS production may hinder the application of ferroptosis inducers in anticancer therapy (Shen et al, 2018; Xie et al, 2016). Activating transcription factor 4 (ATF4) is an essential mediator of endoplasmic reticulum (ER) stress (Bi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although inducing ferroptosis is a promising anticancer strategy, the negative regulators of ferroptosis which inhibit cellular iron uptake and/or limit ROS production may hinder the application of ferroptosis inducers in anticancer therapy (Shen et al, 2018;Xie et al, 2016). Activating transcription factor 4 (ATF4) is an essential mediator of endoplasmic reticulum (ER) stress (Bi et al, 2005).…”
mentioning
confidence: 99%
“…[8] Since discovered in 2012, ferroptosis has been widely known as an iron-and ROS-dependent form of cell death. [9] Catalyzed by Fe 3+ or Fe 2+ (so-called Fenton's reaction), the intracellular hydrogen peroxide (H 2 O 2 ) would be rapidly converted to highly reactive hydroxyl radical (·OH), causing a high ROS stress and resulting in irreversible oxidative damage to lipids, proteins and DNA, eventually cell ferroptosis. [10] More importantly, several studies have found that ferroptotic agents could induce an unfolded protein response and subsequently activated a series of ER stress-mediated ferroptotic signaling pathways, [11] which fits in with our demand for enhanced treatment strategy.…”
mentioning
confidence: 99%